Analisis Peran Guru dalam Meningkatkan Minat Belajar Peserta Didik Kelas IV SDI Betun Kota - Martha Mardiana Olo; Marsela Luruk Bere; Damian Puling; Yohana Febriana Tabun (Jurnal Pendidikan Dirgantara, 2025)
Analysis of the Role of Teachers in Increasing the Learning Interest of Class IV Students of SDI Betun Kota. Guided by Marsela Luruk Bere and Damian Puling, the formulation of the problem in this study is the Analysis of the Role of Teachers in Increasing the Learning Interest of Class IV Students. Teachers have an important role in conveying knowledge to existing students. Not only playing a role in teaching knowledge, there are many roles of teachers in the learning process. The role of teachers in the learning process is: teachers as educators, teachers as instructors, teachers as guides, teachers as influences, teachers as trainers, teachers as assessors. The purpose of this study is to determine the role of teachers in increasing the learning interest of students at SDI Betun Kota. This research was conducted using qualitative methods. The subjects of this study were the Principal, homeroom teacher IV and Class IV Students of SDI Betun Kota. A person's interest is developed to achieve educational goals, this is because interest is a potential that still requires serious and systematic development and training in order to be realized. However, in reality, many students are less interested in a particular subject because of the minimal role of teachers in developing students' talents and interests. How great is the service of a teacher in developing students' talents and interests, the results of this study show that teachers who are effective in increasing students' interest in learning use innovative learning methods, provide motivation, create a conducive learning environment, and have good relationships with students. This study also found that the use of technology in learning can increase students' interest in learning, thus this study contributes to the understanding of the role of teachers in increasing students' interest in learning and can be a reference for teachers and schools in improving the quality of learning.